Depression, sexual dysfunction, and medical comorbidities in young adults having nicotine dependence - Ranjan Bhattacharyya; Debasish Sanyal; Sumita Bhattacharyya; Kaustav Chakraborty; Rajarshi Neogi; Bejoy Bikram Banerjee (Wolters Kluwer Medknow Publications, 2020)
Background: Nicotine dependence, depression, diabetes mellitus, hypertension, and hypothyroidism are risk factors of sexual dysfunction. Aims and Objectives: The present study aims to find the prevalence of sexual dysfunction and the various sexual response cycle domains in individuals with nicotine dependence with and without comorbidities. Materials and Methods: A total of 52 individuals attending the tobacco cessation clinic were included in the study. To assess the primary outcome, Fagerstrom test for nicotine dependence, Arizona Sexual Experiences Scale, and Hamilton's Depression Rating Scale 17had been administered after validation in local vernacular. Results: In the sample, 32 (61.5%) were male and 20 (38.5) were female. The 17 participants (32.7%) met the criteria of low nicotine dependence, 5 (9.6%) participants met low to moderate, 11 participants (21.2%) had moderate dependence, and 19 (36.5%) participants met the criteria of high nicotine dependence. Conclusions: The nicotine dependence is directly related to sexual dysfunction, and it affects various stages of the sexual response cycle. One-quarter of individuals of nicotine dependence also met the threshold criteria of depression. The interventions as primary and primordial preventions with awareness building and health education may be a cost-effective measure to prevent tobacco-related deaths.